Bulk chemical composition of manganese deposits fom the Pacific Ocean - J G Dillard; D L Crowther; Stephen E Calvert (PANGAEA, 2023)
Knowledge of the oxidation states and of the chemical speciation of metals in ferromanganese deposits is of interest to aid in understanding the association of metals with the major oxyhydroxide phases and to gain further insight into the mechanisms of metal uptake. This type of analysis was conducted on ferromanganese nodules and crusts from the Pacific obtained from collections at the Scripps Institution of Oceanography. For the bulk analyses, splits of the nodular material were ground in agate and analyzed by x-ray emission spectroscopy (XRE).